Exploring Communication between Social Workers, Children and Young People. (14th July 2016) - Winter, Karen; Cree, Viviene; Hallett, Sophie; Hadfield, Mark; Ruch, Gillian; Morrison, Fiona; Holland, Sally
Abstract: A key issue for the social work profession concerns the nature, quality and content of communicative encounters with children and families. This article introduces some findings from a project funded by the Economic and Social Research Council (ESRC) that took place across the UK between 2013 and 2015, which explored how social workers communicate with children in their everyday practice. The Talking and Listening to Children (TLC) project had three phases: the first was ethnographic, involving observations of social workers in their workplace and during visits; the second used video-stimulated recall with a small number of children and their social workers; and the third developed online materials to support social workers. This paper discusses findings from the first phase. It highlights a diverse picture regarding the context and content of communicative processes; it is argued that attention to contextual issues is as important as focusing on individual practitioners' behaviours and outlines a model for so doing.